Estimating the Effects of Expanding Ultrasound Use on Sex Selection in India - Mevlude Akbulut-Yuksel; Daniel Rosenblum (Institute of Labor Economics (IZA), 2022)
The liberalization of the Indian economy in the 1990s led to an unprecedented increase in the availability of prenatal ultrasound technology. In this paper, we analyze the differential spread of ultrasound in India at the state level over a ten-year period (1999 to 2008) and the consequences for the prevalence of sex-selective abortion. Omitting the Southern Indian states, which had the fastest increase in ultrasound use and little sex selection, we find that higher levels of ultrasound use within a state are positively associated with the probability that a child is born male. This increased likelihood of having a male child is only found for children with no older brothers, i.e. births most likely to be affected by sex selection. The positive relationship between state-level ultrasound use and having a male child can be found across various subsamples: urban and rural, older and younger mothers, mothers with high and low education. The estimates are robust to including linear cohort-year time trends and prenatal health care controls.
Keywords: J13; J16; O1; 330; sex-selective abortion; gender discrimination; technology adoption; ultrasound; son preference; India